Assessing the Rise of Dedicated Digital Engagement Platforms for Local Planning - Boyco, Morgan (Canadian Planning and Policy / Aménagement et politique au Canada, 2024)
Digitally mediated participation in planning processes has grown significantly. In an emergent digital turn for participatory planning scholarship, there is a growing body of research attempting to trace this growth and grapple with its implications. This paper explores how planning scholars and practitioners can deepen their critical stance toward digital modes of participatory planning. In Canada, this approach becomes especially important given the recent and widespread adoption of a specific digital platform type used to support participatory decision-making at the municipal level. Across the country, many towns and cities have embraced what I call Dedicated Digital Engagement Platforms (DDEPs). Despite their growing influence, these platforms for community involvement have not been previously quantified at a nation-wide level, nor thoroughly examined in planning scholarship. New evidence presented here defines DDEPs and documents the extent of their use by local and regional municipalities across Canada. In light of the growing prominence of these platforms, this article then provides the foundation for a more critical digital participation research agenda that draws on important debates in wider planning theory regarding democratic decision-making, the commercialization of deliberative democracy, and the platformization of public participation.